Non-Contact Detection of Vital Signs Using a UWB Radar Sensor - Zhenzhen Duan; Jing Liang (IEEE Access, 2019)
The ultra-wide band (UWB) radar sensor is useful in the field of mission critical sensors and sensor networks due to its short detection time, high penetration, and low energy consumption. To support critical missions such as search and rescue, this paper designs a non-contact detection system based on a UWB radar sensor module to obtain vital signs of human beings. There are noise and clutter due to non-contact detection, and therefore the coherent background noise removal and moving target display filter are applied. Then, the variational mode decomposition (VMD) algorithm is used to extract heartbeat signals and respiratory signals. In addition, the Hilbert transform is applied to heartbeat signals and respiratory signals to obtain the time-frequency information. The electrocardiogram is also employed to compare the results of the UWB radar sensor. We also detect the human target through-the-wall. It turns out that the system can obtain respiratory and heartbeat characteristics simultaneously in one measurement, saving cost with high accuracy.